The Historical Stages of Tourism Planning and Its Impact in Spreading the Culture of Tourism Development in Libya - Alamouri, Fouziyah Alsadiq Ahmed; Zaidan, Ashraf Mohammed; Abdul Kadir, Fakhrul Adabi (Journal Al-Muqaddimah, 2017)
There are great rapid in the development of the tourism field that it could have serious negative reflections of the receiving area generally, so the state must intervene in organizing and conducting this development by setting precise tourist development plans. Tourism planning is one of the most important ways in contemporary tourism development, as it is an effective indicator of discretionary drawing a picture of the tourism industry in the country, according to a program performs on the steps slotted either long or short term, with specifying the goals of tourist plan to achieve sustainable tourism development. Thus, tourist planning is considered a necessity for sustainable development since tourism has become a substantial economic and social option, so it has become important to be accompanied by culture and tourism awareness among the society to contribute to the success tourism project and its development. Therefore, this paper conducted to study the nature of tourism planning and its relation to spread tourist development culture by studying the reality of tourism in Libya and its significance constituents (nature, humanity), down to the most prominent obstacles tourism in the country and finding out radical solutions to this problem. Moreover, this study aims to link this plan with other plans in other sectors and they should be corresponded to be integrated parts of the general plan of the development in the state. in all world countries, particularly the developing countries; to face competition in the international tourism market